2021
DOI: 10.7150/thno.55645
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the autophagy regulatory network via single-cell transcriptome analysis reveals a requirement for autophagy homeostasis in spermatogenesis

Abstract: Background: Autophagy has been implicated as a crucial component in spermatogenesis, and autophagy dysfunction can lead to reproductive disorders in animal models, including yeast, C. elegans and mice. However, the sophisticated transcriptional networks of autophagic genes throughout human spermatogenesis and their biological significance remain largely uncharacterized. Methods: We profiled the transcriptional signatures of autophagy-related genes durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…B The other network with Tmprss13 and Cst3 as core genes, showing that there is a certain degree of crosstalk between apoptosis and autophagy (See figure on next page.) protein could negatively regulate autophagy in SSCs [34]. An extrapolation of this function would suggest that increased CST3 expression, such as that observed in this study, could suppress autophagy, which is known to contribute to VIDD.…”
Section: Discussionmentioning
confidence: 53%
“…B The other network with Tmprss13 and Cst3 as core genes, showing that there is a certain degree of crosstalk between apoptosis and autophagy (See figure on next page.) protein could negatively regulate autophagy in SSCs [34]. An extrapolation of this function would suggest that increased CST3 expression, such as that observed in this study, could suppress autophagy, which is known to contribute to VIDD.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, the level of autophagy increased in high-fat diet mice with disrupted spermatogenesis and male fertility, and autophagy was also overactivated in sperm samples from obese subfertile male patients [ 41 , 42 ]. Recent studies have found that LAMP2 was highly expressed in human spermatogonia, and some autophagy-related genes were dysregulated in the testicular germ cells of patients with non-obstructive azoospermia (NOA), suggesting that autophagy is related to male infertility [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the widespread applications of gene sequencing, especially scRNA-seq, have deepened the knowledge of NOA [ 25 , 26 ]. For instance, Wang et al had disclosed the unique role of autophagy homeostasis in the spermatogenesis of NOA cases through scRNA-seq analysis [ 27 ]. Liu et al utilized scRNA-seq to detect the genetic change of ACE2 in testicular cells of normal and NOA patients, uncovering the possible mechanisms of how SARS-CoV-2 affected testicular cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%